2018
DOI: 10.1166/jnn.2018.14865
|View full text |Cite
|
Sign up to set email alerts
|

Thymosin β4 Reduces H2O2 Induced Oxidative Stress in MC3T3-E1 Cells on Titanium Surface

Abstract: Thymosin β4 (Tβ4) is known to inhibit an inflammatory response and to increase the survival of osteoblasts on titanium (Ti) surfaces. Ti is the most widely used graft material in dentistry; however, an inflammatory response induced following implant placement results in the generation of reactive oxygen species (ROS). The oxidative stress from the production of ROS such as nitric oxide (NO) and hydrogen peroxide (H2O2) can damage surrounding cells, resulting in implant failure by decreasing cell viability. Thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Oxidative stress greatly influences the viability, proliferation, and survival of osteocytes 29 . In this study, we used 0.2 mM H 2 O 2 to generate a model of oxidative damage according to a previous study 30 . We observed that after treatment with 0.2 mM H 2 O 2 , the viability and osteogenic differentiation capacity of cells was decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress greatly influences the viability, proliferation, and survival of osteocytes 29 . In this study, we used 0.2 mM H 2 O 2 to generate a model of oxidative damage according to a previous study 30 . We observed that after treatment with 0.2 mM H 2 O 2 , the viability and osteogenic differentiation capacity of cells was decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Tβ4 treatment has been shown to reduce the release of ROS and inflammation. 40 In addition, growing evidence shows that Tβ4 is involved in antioxidant, anti-inflammatory and antifibrotic responses to liver injury. 18 , 39 , 41 , 42 It has also been reported that the serum Tβ4 concentration is closely related to the severity of hepatic injury.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in scar tissue has been observed by multiple research groups in different animal models of injury, including excisional wounds, myocardial infarct, stroke, and fibrosis of the lung, liver, and kidney [44][45][46][47][48][49][50][51] (table 2). Thymosin ␤4 reduces oxidative stress by targeting anti-oxidative genes [52][53][54][55][56][57]. It reduced toxicity by inhibiting inducible nitric oxide synthetase (iNOS) and cyclooxygenase-2, resulting in decreased reactive oxygen species (ROS), decreased secretion of NO, and decreased prostaglandins.…”
Section: Thymosin ␤4 Regenerative Activitiesmentioning
confidence: 99%